2009
DOI: 10.1016/j.juro.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ileum as Ureteral Replacement in Urological Reconstruction

Abstract: Purpose-We reviewed indications and outcomes in patients undergoing ileal ureter replacement for ureteral reconstruction. December 1989 and September 2007, 105 patients underwent ileal ureter replacement, of whom 14 were excluded from study due to incomplete data. The remaining 91 patients (99 renal units) comprised the study cohort. Materials and Methods-BetweenResults-Mean patient age was 46.8 years and mean followup was 36.0 months. Indications for an ileal ureter were stricture following genitourinary sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(108 citation statements)
references
References 18 publications
5
93
1
8
Order By: Relevance
“…Multiple studies have confirmed the utility and reliability of ureteral replacement with small intestine [9,10]. However, we counsel patients preoperatively that the complication rate ranges from about 30 to 50%-minor mostly and major less often.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Multiple studies have confirmed the utility and reliability of ureteral replacement with small intestine [9,10]. However, we counsel patients preoperatively that the complication rate ranges from about 30 to 50%-minor mostly and major less often.…”
Section: Discussionmentioning
confidence: 94%
“…Having any of these could lead to worsening renal failure and/or bowel related shortterm and long-term complications. Armatys et al describe a 7-shaped and reverse 7-shaped ileal segment configuration for bilateral ureteral reimplantation [9]. The disadvantage of this is technique is that it can be difficult to position the middle ileal segment to the renal pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…По данным литературы, после открытой пла-стики мочеточника кишкой в 10% случаев наблю-даются такие отдаленные осложнения, как негер-метичность анастомоза, стриктура и фистула [2][3][4].…”
Section: оригинальные статьиunclassified
“…В настоящее время кишечная пластика мо-четочника является методом выбора при протя-женных рецидивных стриктурах верхних мочевых путей (ВМП) [1][2][3][4]. Данная операция до эры эн-довидеохирургии выполнялась открытым досту-пом, который был травматичным и значительно увеличивал сроки пребывания в стационаре и ре-абилитации больных.…”
unclassified
“…Options for ureteral replacement traditionally include psoas hitch, boari flap, the Monti tube, use of the appendix, reconfigured colon or ileal segment (Brandes et al, 2004;Mathews &Marshal,1997;Ali-El-Dein&Ghoneim,2003;Jeffrey et al,2000;Armatys et al,2009;Pope&Koch,1996). Ureteral defects too long to be treated by excision and spatulated end-toend anastomosis can be treated by use of oral mucosa grafts.…”
Section: Use Of Oral Mucosal Grafts For Ureteral Replacementmentioning
confidence: 99%